Lignin Derived Porous Carbons: Synthesis Methods and Supercapacitor Applications. Issue 11 (7th October 2021) - Zhang, Wenli; Yin, Jian; Wang, Caiwei; Zhao, Lei; Jian, Wenbin; Lu, Ke; Lin, Haibo; Qiu, Xueqing; Alshareef, Husam N.
Abstract: Lignin, one of the renewable constituents in natural plant biomasses, holds great potential as a sustainable source of functional carbon materials. Tremendous research efforts have been made on lignin‐derived carbon electrodes for rechargeable batteries. However, lignin is considered as one of the most promising carbon precursors for the development of high‐performance, low‐cost porous carbon electrode materials for supercapacitor applications. Yet, these efforts have not been reviewed in detail in the current literature. This review, therefore, offers a basis for the utilization of lignin as a pivotal precursor for the synthesis of porous carbons for use in supercapacitor electrode applications. Lignin chemistry, the synthesis process of lignin‐derived porous carbons, and future directions for developing better porous carbon electrode materials from lignin are systematically reviewed. Technological hurdles and approaches that should be prioritized in future research are presented. Abstract : Lignin‐derived porous carbon materials are promising for future low‐cost supercapacitor electrodes. This review covers lignin chemistry and methods for synthesizing lignin‐derived porous carbons (LDPCs). It also discusses the recent research development and future research directions of LDPCs for supercapacitor applications.